Machado de Assis e a língua portuguesa no Brasil no fim do Império: aspectos da história do negro em crônicas da série Bons Dias! - Toscano, Diego Marsalla (2008)
This Dissertation works cronics of collection Bons Dias!, by Machado de Assis and it pretends to show in historic and intellectual context that these documents were produced the contextual influences express in theirs and to check questions of orthography and accentuation as grammatical marks of portuguese language s use in a second half from century XIX. In face of that, the justification of that study appears in the proportion to reveal the social importance to reflect the Machado de Assis s cronics and the context linguistic-cultural of final s century XIX. The Machado de Assis s cronics reflects grammatical marks is registered in the compendium of this epoch, specifically in a Grammatica Portugueza, by Julio Ribeiro, and it makes possible to perpetuate aspects of Brazilian s black people in the slave s times in the Brazil. The theory is Historiography Linguistics, worked in the perspectives pointed from Konrad Koerner (1989, 1995, 1996), and it considers the approximations of Linguistics and History in the process of comprehension and interpretation of linguistics phenomenon. This discipline makes possible that language s historiographer finds answers for portuguese language s comprehension in use in the Brazil in past and its relation with the present time by verification of its register in two times. Therefore, in the selected cronics, marks of orthography and accentuation of portuguese language and of cronic that time is checked by application of metalanguage recourse. In a historiography perspective, the metalanguage furthers observations about historic-linguistics and it avoids distortions in the process of interpretation. After that, we works the beginnings of contextualization historic and intellectual, immanence and adequacy theorist that works together for the exam of old documents and its respective registers linguistics. The results obtained shows the idea that these Machado de Assis s cronics are documents historic-linguistics and we can identify un dialogue between reality and fiction and it materialize social, grammatical and linguistics aspects from context specific in these documents were produced